An introduction to the EULAR–OMERACT rheumatoid arthritis MRI reference image atlas. (12th January 2005) - Østergaard, M; Edmonds, J; McQueen, F; Peterfy, C; Lassere, M; Ejbjerg, B; Bird, P; Emery, P; Genant, H; Conaghan, P
Abstract : This article gives a short overview of the development and characteristics of the OMERACT rheumatoid arthritis MRI scoring system (RAMRIS), followed by an introduction to the use of the EULAR–OMERACT rheumatoid arthritis MRI reference image atlas. With this atlas, MRIs of wrist and metacarpophalangeal joints of patients with rheumatoid arthritis can be scored for synovitis, bone oedema, and bone erosion, guided by standard reference images.